A study on abnormal pattern recognition using mahalanobis distance for local exhaust ventilation system - Nor Hafizah, Abd Rauf (2012)
Local Exhaust Ventilation (LEV) systems can afford a very efficient means of exposure control. Ventilation is a practical system for controlling the air quality and thermal exposure that the employees meet. Ventilation can be used to eliminate air contaminant from breathing district of the employees. Local Exhaust Ventilation (LEV) is employ to eliminate contaminants that are generated at a local supply. Air is drawn from a source at a rate competent of eliminating any air contaminants generated at that supply before they can be dispersed into the work surroundings. There is a problem with conventional method in measuring the LEV, which is time consuming. The conventional method is tedious because it takes longer time to measure the LEV. The objective of this research is to introduce new approach of LEV monitoring practice (Mahalanobis Distance recognition). By using Mahalanobis Distance (MD) with Excel Based Programmed, the method in measuring LEV will be easier and faster. It is believe that this new method is one of the first attempts to evaluate LEV performance by using multi-dimensional approach.